The Mechanisms of Coastal Erosion in Northeast Bali - Semeidi Husrin; Roka Pratama; Aprizon Putra; Hadi Sofyan; Nia Naelul Hasanah; Nita Yuanita; Irwan Meilano (Pusat Riset Kelautan, 2016)
Marine tourism sector in the Northeast Bali, Indonesia, experienced rapid development in the last decades. However, severe coastal erosion in some parts of the area has threaten the industry. Unsuccessful mitigation measures have been carried out by authorities by constructing seawalls along the coastline. The objective of the study is to understand the physical processes related to coastal erosion in the area and to assess the effectiveness of seawall along the coastline. To achieve the objectives, a GIS approach was carried out to investigate general changes of the coastline since 1944 until 2013. Hydrodynamics analyses and sediment transport simulations were also conducted and validated by the data from field measurements. The role of Mount Agung (a volcanic mountain) to the coastal dynamic system was also investigated. Moreover, the data from cGPS measurements in the island were also used for the analysis of possible land subsidence in the area. From social aspects, the history of USAT Liberty Shipwreck in Tulamben Village supports the analyses and provides information on the evolution of coastline in the area. We conclude that coastal erosion in North-east Bali has long been occurred and strongly affected by the dynamics of hydro-oceanography, volcanic activities, geological dynamics, and human interferences. Finally, the mechanism of coastal erosion in the area was also proposed.